Perancangan Aplikasi Panduan Belajar Gerakan Tunarungu Menggunakan Adobe Flash - Ratna Juliani Siregar; Syaiful Zuhri Harahap (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2022)
Deafness is one type of disability that is quite widely available in Indonesia, either experiencing it congenital or due to other factors where people with this disability experience a lack or loss of hearing ability so that they experience obstacles in language development. Deaf children still have the potential to learn to speak and speak. Therefore, deaf children need special services or media to develop language and speaking skills so as to minimize the impact of deafness experienced. Therefore, parents and teachers are obliged to guide children with hearing impairment to learn sign language. Currently, online education facilities are very attractive for children to learn. In fact, there are many developers who create modules, educational games, learning applications, tutorials, and more on Android. But not so for children with disabilities, especially deaf, Learning media is more likely to facilitate normal children. In fact, the learning materials and curricula of normal schools and special schools are the same, only the form of delivery is different. There are not many learning media for deaf children to learn, only the form of tutorials is limited to the introduction of the alphabet without any facilities to be able to deepen sign language itself. Deaf people need and deserve the same learning media as normal children.